Reactions of Chlorambucil and its main metabolite, Phenylacetic Acid Mustard, with 2’-deoxyribonucleosides and Calf Thymus DNA - Florea-Wang, Diana (fi=Turun yliopisto|en=University of Turku|, 2009)
Chlorambucil is an anticancer agent used in the treatment of a variety of cancers, especially in chronic lymphocytic leukemia, and autoimmune diseases. Nevertheless, chlorambucil is potentially mutagenic, teratogenic and carcinogenic. The high antitumor activity and high toxicity of chlorambucil and its main metabolite, phenylacetic acid mustard, to normal tissues have been known for a long time. Despite this, no detailed chemical data on their reactions with biomolecules in aqueous media have been available. The aim of the work described in this thesis was to analyze reactions of chlorambucil with 2’-deoxyribonucleosides and calf thymus DNA in aqueous buffered solution, at physiological pH, and to identify and characterize all adducts by using modern analyzing methods. Our research was also focused on the reactions of phenylacetic acid mustard with 2’-deoxynucleosides under similar conditions. A review of the literature consisting of general background of nucleic acids, alkylating agents and ultraviolet spectroscopy used to identify the purine and pyrimidine nucleosides, as well as the results from experimental work are presented and discussed in this doctoral thesis.